Shark lady : the true story of how Eugenie Clark became the ocean's most fearless scientist - Keating, Jess (Sourcebooks Jabberwocky, 2017)
At 9 years old, Eugenie Clark developed an unexpected passion for sharks after a visit to the Battery Park Aquarium in New York City. At the time, sharks were seen as mindless killing machines, but Eugenie knew better and set out to prove it. Despite manyobstacles in her path, Eugenie was able to study the creatures she loved so much. From her many discoveries to the shark-related myths she dispelled, Eugenie's wide scientific contributions led to the well-earned nickname "Shark Lady"--